Scaffolding or Enabling? Implications of Extended Parental Financial Support into Adulthood - David Tenerelli; Sharon Weaver; Nathan Astle; Megan A McCoy (Journal of Financial Therapy, 2019)
Recent decades have seen tremendous changes in the duration of time that parents offer financial support to their adult children. This paper explores the literature regarding the variations in support, the forces impacting those variations, and the effects of that support on the children's human capital and financial attainment, as well as implications for parents. A case vignette based on an amalgam of case experiences by the authors is provided to explore the relevance of the literature findings to an amalgam financial planning client in the situation of providing financial support to an adult child. Sample interventions are based on the theoretical framework of Bowen’s family systems theory and Archuleta’s Couples and Finances Theory.
Keywords: financial enmeshment; extended adolescence; Bowen’s Family System Theory; Archuleta’s Couples and Finance Theory